Molecular characterization of the gene profile of Bacillus thuringiensis Berliner isolated from Brazilian ecosystems and showing pathogenic activity against mosquito larvae of medical importance - Soares-da-Silva, Joelma; Queiros, Silmara Gomes; Aguiar, Jessica S. de; Viana, Juliete L.; Neta, Maria dos R. A. V.; Silva, Maria C. da; Pinheiro, Valeria C. S.; Polanczyk, Ricardo A. [UNESP]; Carvalho-Zilse, Gislene A.; Tadei, Wanderli P. (Elsevier B.V., 2017)
The occurrence of Aedes aegypti, Culex quinquefasciatus, and mosquitoes of the genus Anopheles potentiate the spread of several diseases, such as dengue, Zika, chikungunya, urban yellow fever, filariasis, and malaria, a situation currently existing in Brazil and in Latin America. Control of the disease vectors is the most effective tool for containing the transmission of the pathogens causing these diseases, and the bacterium Bacillus thuringiensis var. israelensis has been widely used and has shown efficacy over many years. However, new B. thuringiensis (Bt) strains with different gene combinations should be sought for use as an alternative to Bti and to prevent the resistant insects selected. Aiming to identify diversity in the Bt in different Brazilian ecosystems and to assess the pathogenicity of this bacterium to larvae of Ae. aegypti, C. quinquefasciatus, and Anopheles darlingi, Bt strains were obtained from the Amazon, Caatinga (semi-arid region), and Cerrado (Brazilian savanna) biomes and tested in pathogenicity bioassays in third-instar larvae of Ae. aegypti under controlled conditions in the laboratory. The isolates with larvicidal activity to larvae of Ae. aegypti were used in bioassays with the larvae of C. quinquefasciatus and An. darlingi and characterized according to the presence of 14 cry genes (cry1, cry2, cry4, cry10, cry11, cry24, cry32, cry44Aa, cry1Ab, cry4Aa, cry4Ba, ctyl0Aa, cry11Aa, and cry11Ba), six cyt genes (cyt1, cyt2, cyt1Aa, cyt1Ab, cyt2Aa and cyt2Ba), and the chi gene. Four hundred strains of Bt were isolated: 244 from insects, 85 from Amazon soil, and 71 from the Caatinga biome. These strains, in addition to the 153 strains isolated from Cerrado soil and obtained from the Entomopathogenic Bacillus Bank of Maranhao, were tested in bioassays with Ae. aegypti larvae. A total of 37 (6.7%) strains showed larvicidal activity, with positive amplification of the cry, cyt, and chi genes. The most frequently amplified genes were cry4Aa and cry4Ba, both occurring in 59.4% in these strains, followed by cyt1Aa and cyt2Aa, with 56.7% and 48% occurrence, respectively. Twelve (2.2%) strains that presented 100% mortality within 24 h were used in bioassays to estimate the median lethal concentration (LC50) for Ae. aegypti larvae. Two strains (BtMA-690 and BtMA-1114) showed toxicity equal to that of the Bti standard strain, and the same LC50 value (0.003 mg/L) was recorded for the three bacteria after 48 h of exposure. Detection of the presence of the Bt strains that showed pathogenicity for mosquito larvae in the three biomes studied was possible. Therefore, these strains are promising for the control of insect vectors, particularly the BtMA-1114 strain, which presents a gene profile different from that of Bti but with the same toxic effect.
Keywords: Mosquitoes vectors; Biological control; Bacteria; Genes cry e cyt